Physical activity levels in locally advanced rectal cancer patients following neoadjuvant chemoradiotherapy and an exercise training programme before surgery: a pilot study. Issue 1 (December 2017) - Loughney, Lisa; West, Malcolm; Dimitrov, Borislav; Kemp, Graham; Grocott, Michael; Jack, Sandy
Abstract Background The aim of this pilot study was to measure changes in physical activity level (PAL) variables, as well as sleep duration and efficiency in people with locally advanced rectal cancer (1) before and after neoadjuvant chemoradiotherapy (CRT) and (2) after participating in a pre-operative 6-week in-hospital exercise training programme, following neoadjuvant CRT prior to major surgery, compared to a usual care control group. Methods We prospectively studied 39 consecutive participants (27 males). All participants completed standardised neoadjuvant CRT: 23 undertook a 6-week in-hospital exercise training programme following neoadjuvant CRT. These were compared to 16 contemporaneous non-randomised participants (usual care control group). All participants underwent a continuous 72-h period of PA monitoring by SenseWear biaxial accelerometer at baseline, immediately following neoadjuvant CRT (week 0), and at week 6 (following the exercise training programme). Results Of 39 recruited participants, 23 out of 23 (exercise) and 10 out of 16 (usual care control) completed the study. In all participants (n = 33), there was a significant reduction from baseline (pre-CRT) to week 0 (post-CRT) in daily step count: median (IQR) 4966 (4435) vs. 3044 (3265);p < 0.0001, active energy expenditure (EE) (kcal): 264 (471) vs. 154 (164);p = 0.003, and metabolic equivalent (MET) (1.3 (0.6) vs. 1.2 (0.3);p = 0.010). There was a significant improvement in sleep efficiency (%) between week 0 and week 6 in the exercise group compared to the usual care control group (80 (13) vs. 78 (15) compared to (69 ((24) vs. 76 (20);p = 0.022), as well as in sleep duration and lying down time (p < 0.05) while those in active EE (kcal) (152 (154) vs. 434 (658) compared to (244 (198) vs. 392 (701) or in MET (1.3 (0.4) vs. 1.5 (0.5) compared to (1.1 (0.2) vs. 1.5 (0.5) were also of importance but did not reach statistical significance (p > 0.05). An apparent improvement in daily step count and overall PAL in the exercise group was not statistically significant. Conclusions PAL variables, daily step count, EE and MET significantly reduced following neoadjuvant CRT in all participants. A 6-week pre-operative in-hospital exercise training programme improved sleep efficiency, sleep duration and lying down time when compared to participants receiving usual care. Trial registration Clinicaltrials.govNCT01325909